Advances in Computer Communication and Computational Sciences Proceedings of IC4S 2018 - Bhatia, Sanjiv K.; Tiwari, Shailesh; Mishra, Krishn K.; Trivedi, Munesh C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book includes key insights that reflect 'Advances in Computer and Computational Sciences' from upcoming researchers and leading academics around the globe. It gathers high-quality, peer-reviewed papers presented at the International Conference on Computer, Communication and Computational Sciences (IC4S 2018), which was held on 20-21 October, 2018 in Bangkok. The book covers a broad range of topics, including intelligent hardware and software design, advanced communications, intelligent computing techniques, intelligent image processing, and web and informatics. Its goal is to familiarize readers from the computer industry and academia with the latest advances in next-generation computer and communication technology, which they can subsequently integrate into real-world applications.
Software Architecture Decision-Making Practices and Recommendations -- Abstraction in Modeling and Programming with Associations: Instantiation, Composition and Inheritance -- A Collaborative Model for Customer Retention on User Service Experience -- Remote Collaborative Live Coding in SuperCollider-Based Environments via Open Sound Control Proxy -- A Collaborative Model for Customer Retention on User Service Experience -- Smart Services for Smart Cities: New Delhi Versus Jaipur -- Effect of Constraint Variation on the Efficiency of Protocols Under Realistic Environment -- Energy Efficient Improved SEP for Routing In Wireless Sensor Networks -- Content Based Audio Classification and Retrieval Using Segmentation, Feature Extraction and Neural Network Approach -- Information Extraction from Natural Language Using Universal Networking Language -- Towards Improving Performance of Sigma Filter -- Review Of Camera Calibration Algorithms. .
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence